2022
DOI: 10.3389/fnsyn.2022.748184
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Assembly of Subsynaptic Nanoscale Organizations During Development

Abstract: Nanoscale organization of presynaptic proteins determines the sites of transmitter release, and its alignment with assemblies of postsynaptic receptors through nanocolumns is suggested to optimize the efficiency of synaptic transmission. However, it remains unknown how these nano-organizations are formed during development. In this study, we used super-resolution stochastic optical reconstruction microscopy (STORM) imaging technique to systematically analyze the evolvement of subsynaptic organization of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
4
12
0
Order By: Relevance
“…4F, right) and area (Table 4-1; Fig. 4G, right) of PSD-95 NCs increased substantially after the first week, similar to what has been observed previously (Sun et al, 2022). Additionally, PSD-95 Δdensity did not change across development for alone or paired synapses (Table 4-1; Fig.…”
Section: Resultssupporting
confidence: 87%
“…4F, right) and area (Table 4-1; Fig. 4G, right) of PSD-95 NCs increased substantially after the first week, similar to what has been observed previously (Sun et al, 2022). Additionally, PSD-95 Δdensity did not change across development for alone or paired synapses (Table 4-1; Fig.…”
Section: Resultssupporting
confidence: 87%
“…Co‐staining with antibodies of two rabbit origins (rabbit anti‐GluA1, ab31232, 1:200; rabbit anti‐RIM1/2) was performed as described. [ 29 ] In brief, staining was performed separately, the first primary antibody (rabbit anti‐GluA1) was blocked and converted with a goat anti‐rabbit Fab fragment (Jackson Immuno, 111‐007‐003, 1:100) for 1.5 h at room temperature. After washing with PBS plus 50‐mM glycine, primary antibodies (rabbit anti‐RIM1/2) were incubated for 3 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we document variability in molecular characteristics of presynaptic release sites within a single active zone and show that NMDAR subsynaptic distribution is dependent on highly local transcellular context. Other recent work has shown that postsynapses contain diverse scaffold molecules beyond PSD-95 that are organized in unique and developmentally regulated NCs 10,71,72 . Synaptic nanoclustering and trans-synaptic alignment are conserved in evolution and observed across several synapse types 40,73,74 , the detailed characteristics of which depend on cleftresident synaptic organizing complexes 1,9,11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we document variability in molecular characteristics of presynaptic release sites within a single active zone and show that NMDAR subsynaptic distribution is dependent on highly local transcellular context. Other recent work has shown that postsynapses contain diverse scaffold molecules beyond PSD-95 that are organized in unique and developmentally regulated NCs 10,71,72 .…”
Section: Discussionmentioning
confidence: 99%